PET/CT in the management of primary angiosarcoma of the heart - Todorova-Stefanovski D; Spirov G; Tasevski S; Beshliev S; Angjeleska M.; Ugrinska, Ana (My University, 2022)
INTRODUCTION Primary cardiac tumors are rare and mostly benign, with only 30% of them being malignant. The most common pathological type is angiosarcoma, which mainly affects the right atrium and has a fatal prognosis with survival of 3-11months. It is very important to make a difference patohistologically with epitheloid hemangioendothelioma, which has low to medium potential to metastasize and better prognosis from the angiosarcoma. CASE REPORT 35 years old, 9 months pregnant woman was diagnosed with a tumor in the right atrium. The tumor was surgically removed and the baby delivered in one instance. The first histopathology reported epithelioid hemangioendothelioma. The patient was referred for a PET/CT scan. The results showed increased FDG uptake in the right atrium (SUVmax=7.3), consistent with residual tumor or postoperative inflammation, and multiple bone metastases (SUVmax=5.4). After the PET scan histopathology was reviewed once again and the second report was in concordance with angisarcoma of the heart . After 4 cycles of chemotherapy, PET/CT was performed for restaging and treatmenmt response assesment and it showed progression of the disease with local recidiv (SUVmax=5.8), lymph nodes, bilateral adrenal (SUVmax=6.1) and hepatic metastases (SUV max=4.6). Despite haemotherapy the disease rapidly progressed and patient died 11 months after the diagnosis. CONCLUSION The imaging diagnostic workup in cardiac tumors is not well established yet. The case report that we’ve presented illustrates the role of FDG /PET in the assessment of malignant potential of the primary tumor, and in staging and restaging of the disease.